2009
DOI: 10.1111/j.1530-0277.2009.01003.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Cognitive and Emotion Processing Abilities of Children With Fetal Alcohol Spectrum Disorders: A Comparison With Attention Deficit Hyperactivity Disorder

Abstract: Children with FASDs show a distinct behavioral profile from children with ADHD. Difficulties in social cognition and emotion processing in children with FASDs may contribute to their high incidence of social behavioral problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
104
2
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(120 citation statements)
references
References 91 publications
12
104
2
2
Order By: Relevance
“…28 Another study of children with FASD compared with children with ADHD revealed that children with FASD were more likely than the ADHD group to engage in sociopathic behaviors, such as lying and stealing. 29 Greenbaum et al 30 found that children with FASD demonstrate a behavioral profile distinct from children with ADHD, especially related to difficulties in social cognition and emotion processing. These differences and the lack of recognition of FASD have significant implications for the pharmacologic and therapeutic approach to treating the child, since studies have demonstrated differential response to medication for children with FASD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Another study of children with FASD compared with children with ADHD revealed that children with FASD were more likely than the ADHD group to engage in sociopathic behaviors, such as lying and stealing. 29 Greenbaum et al 30 found that children with FASD demonstrate a behavioral profile distinct from children with ADHD, especially related to difficulties in social cognition and emotion processing. These differences and the lack of recognition of FASD have significant implications for the pharmacologic and therapeutic approach to treating the child, since studies have demonstrated differential response to medication for children with FASD.…”
Section: Discussionmentioning
confidence: 99%
“…15,26,27 However, there are qualitative differences in the types of attention problems seen in children with FASD as compared with children with ADHD. [28][29][30] Children with ADHD and FASD have been shown to have greater deficits in verbal comprehension and perceptual reasoning than children having ADHD without prenatal alcohol exposure. 28 Another study of children with FASD compared with children with ADHD revealed that children with FASD were more likely than the ADHD group to engage in sociopathic behaviors, such as lying and stealing.…”
Section: Discussionmentioning
confidence: 99%
“…Four North American studies assessed predominantly African American (83%-94%) 24,30 or exclusively African American cohorts. 32,33 In addition to PAE/FASD groups, 3 studies included subgroups with attention-deficit/hyperactivity disorder (ADHD), 15,26,34 and 1 study included a subgroup with prenatal cocaine exposure (Supplemental Appendix 2). 33 Additional data (eg, individual group sample size data) were requested for 3 articles, 17,23,29 but authors were unable to access archives (n = 2) or did not respond (n = 1).…”
Section: Literature Searchmentioning
confidence: 99%
“…After screening and review, 23 articles were included in qualitative or quantitative analysis, with between 2 and 8 articles (total: 16) included in various meta-analyses. Tables 3 and 4 show the characteristics of included studies, according to presence of FASD (10 studies) [13][14][15][16][17][18][19][20][21] or PAE (14 studies), respectively [22][23][24][25][26][27][28][29][30][31][32][33][34] : one study reported data for both PAE and FASD. 35 Most were from North America (n = 15; 65.2%), followed by Australia (n = 4) and Canada (n = 2), with 1 study each from Finland and Taiwan.…”
Section: Literature Searchmentioning
confidence: 99%
“…A number of such human disorders, albeit mechanistically and causally perhaps unrelated, are characterized by abnormal social behaviour. For example, symptoms and/or diagnostic criteria of Autism Spectrum Disorders (ASD), schizophrenia or fetal alcohol spectrum disorders (FASD) all contain some form or level of social behaviour abnormality (Gillberg et al, 1996;Greenbaum et al, 2009;Hoertnagl & Hofer, 2014). These disorders represent substantial unmet medical needs mostly because their mechanisms and/or causes are poorly understood, and thus development of proper treatments has been difficult.…”
Section: Shoaling and The Dopaminergic System In Zebrafishmentioning
confidence: 99%